Komposisi Gulma Dan Pertumbuhan Padi Sawah Pada Aplikasi Teknologi Budidaya Tanpa Olah Tanah Dan Frekuensi Penyiangan - Rahmat Muhidin; Jenal Mutakin; Ardli Swardana; Rahmi Fatimah; Maryati Puspitasari (Jurnal Penelitian Pertanian Terapan, 2025)
The purpose of this study is to analyze the composition of weeds and the growth of lowland rice influenced by the use of TOT cultivation technology and varying weeding frequencies. The study was carried out between June and November 2024. The approach employed in this research was an experimental method utilizing a split plot design, with two primary factors: the application of cultivation technology (B), featuring two treatment conditions, and the frequency of weeding (F), with six different levels of treatment. A combination of treatment plots was established for each block. Weed samples were taken at 7 points in each combination plot diagonally, using a square freem of 50cm x 50cm. Weed identification results were analyzed for dominance values (S.D.R) and Diversity Index (H') based on Shannon-Wiener. Data on weed dry weight and paddy growth obtained were analyzed using ANOVA, with a further DRMT (Duncan) test at the 5% level.Result of the research show that TOT cultivation technology and weeding frequency have a significant effect on weeds and rice growth. The most weeds were found in the conventional system with 37 species with the dominant weed being Cynodon dactylon for those that were not weeded and Pistia stratiotes for those that were weeded. In the TOT system, 24 species were found with the dominant weed Pistia stratiotes in both weeded and unlit fields, with the diversity index in each treatment being moderate. A weeding frequency of 3 times provides the lowest dry weight of weeds. on the number of tillers at the age of 40 DAP and the frequency of competition had the best effect on weed suppression and the number of leaves per hil